Nusyuz dalam Fiqh dan Praktik Modern - Husnul Furqon; Heri Firmansyah (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the concept of nusyuz from a classical Islamic jurisprudence perspective and its relevance in modern legal practice, against the backdrop of tensions between patriarchal understandings of Islamic jurisprudence and the values ​​of equality and justice. This study employed a normative legal method (library research) with a juridical-normative and conceptual approach, and analyzed qualitatively through content analysis and the maqasid al-sharia approach. The results indicate that the concept of nusyuz in classical Islamic jurisprudence is primarily directed toward wives, based on Surah An-Nisa', verse 34, while the concept of nusyuz for husbands, in Surah An-Nisa', verse 128, is less developed proportionally. In modern legal practice in Indonesia, this concept is still used in the Compilation of Islamic Law and religious courts, but has shifted toward a more contextual and equitable approach. Therefore, a reconstruction of the understanding of nusyuz is necessary to align it with the principles of justice and equality, so that it is no longer understood as a form of domination, but rather as a violation of shared commitments within the household that can be committed by both parties.